1997
DOI: 10.1074/jbc.272.30.18817
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Roles of the Conserved Amino Acids in Human Liver Mitochondrial Aldehyde Dehydrogenase

Abstract: The sequence alignment of all known aldehyde dehydrogenases showed that only 23 residues were completely conserved (Hempel, J., Nicholas, H., and Lindahl, R. (1993 Oxidation of toxic aldehydes to their corresponding acids is primarily catalyzed by aldehyde dehydrogenase (ALDH).1 During the last two decades, several ALDHs from different organisms were discovered. By aligning the sequences of 16 known ALDHs, it was found that only 23 amino acids were completely conserved (1). More recently, Vasiliou et al. (2) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 27 publications
(39 reference statements)
3
79
0
Order By: Relevance
“…Hurley et al (15) have found that mutation of Arg-475 in ALDH2 leads to disorder in the co-factor binding region through a "domino effect." And Sheikh et al (22) observe that mutation of Ser-471 to an alanine results in a 50-fold increase in the K m for NAD. An even more striking effect of a distal mutation on the NAD binding site was described for the naturally occurring ALDH2:E487K mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Hurley et al (15) have found that mutation of Arg-475 in ALDH2 leads to disorder in the co-factor binding region through a "domino effect." And Sheikh et al (22) observe that mutation of Ser-471 to an alanine results in a 50-fold increase in the K m for NAD. An even more striking effect of a distal mutation on the NAD binding site was described for the naturally occurring ALDH2:E487K mutation.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of class 1 and 2 ALDHs, the likely candidate to abstract a proton from Cys-302 is Glu-268 (5,10,20,22). The glutamate then shuttles the proton to bulk water before participating in the deacylation step of the reaction (10,25).…”
Section: Discussionmentioning
confidence: 99%
“…In the second step, an activated water molecule hydrolyzes the thioester, releasing the product. It has been suggested that deprotonation of the catalytic cysteine prior to the nucleophilic attack on the substrate, a required step in this mechanism, involves acceptance of a proton by either glutamate 268 or 399 (5,7,20,(22)(23)(24). The resulting thiolate ion is likely stabilized by the positively charged nic-otinamide ring of the coenzyme and/or adjacent main chain amide groups.…”
mentioning
confidence: 99%
“…The deduced polypeptide consists of 501 amino acids with a predicted molecular mass of 54.3 kD. Its sequence contains the conserved residues that have been identified in Homo sapiens (human) liver ALDH as active site amino acids (Sheikh et al, 1997;Yoshida et al, 1998). The lack of N-or C-terminal extensions as compared with the mammalian liver ALDH suggests that REF1 is likely to be tetrameric (Rodriguez-Zavala and Weiner, 2002).…”
Section: Ref1 Belongs To a Family Of Aldhs In A Thalianamentioning
confidence: 99%